Thermal Performance of Horizontally/Vertically Oriented Piezoelectric Fans in Varying Fin-Array Width. Issue 15 (31st May 2021) - Uç, Erol; Ekici, Özgür
Abstract: Piezoelectric fan driven forced convection is investigated with a three-dimensional numerical model by employing a dynamic mesh technique for varying fin-array width with increasing number of fins. Two different types of boundary settings have been tested. In the boundary setting-I, a fixed heat flux value distributed uniformly among the fins, whereas a constant heat flux is applied to the base of each fin in the boundary setting-II. Comparisons are made by investigating the heat transfer augmentation ratio and the average surface temperature of fin blocks. Applying the first criterion, the 2-fin-block configuration for the boundary setting-I and the 1-fin-block configuration for the boundary setting-II gives the best results for the horizontal fan arrangement. For the same boundary settings, I and II, differences between the average surface temperatures obtained with and without the piezoelectric fan reaches their maximum, respectively in 1-fin-block and 3-fin-block configurations. Besides, a vertical fan arrangement is employed and noticeably less variation in the cooling performance with varying fin-array width is obtained in comparison to the horizontal fan arrangement. The horizontal fan arrangement is found to provide better cooling performance although the cooling performance of horizontal and vertical arrangements are approaching to each other with increasing fin-array width.